Pengaruh Partisipasi Penyusunan Anggaran Terhadap Kinerja Pegawai Dengan Komitmen Organisasi Dan Gaya Kepemimpinan Sebagai Variabel Moderating(Survey pada Dinas Tenaga Kerja Dan Transmigrasi Kabupaten Wonogiri) - Artiani, Nafiah, Drs. Eko Sugiyanto, M.Si (2016)
Budget participation process involving many parties, starting from the top-level management to lower levels of management. Aspects of human resources as a constituent and executors of the budget should be considered, because the budget will be influenced by human behavior, especially for those directly involved in the preparation and implementation of the budget. Success in managing an organization can not be separated from the organization's leadership and commitment to a high level of an organization, it certainly will try our best to do every activity in the interest of the organization. The purpose of this study was to determine the influence of organizational commitment and leadership style on the relationship of budget participation with employee performance. This study used a survey method using primary data obtained through questionnaires. The population in this study were all employees of the Department of Labor and Transigrasi Wonogiri. The number of samples taken in this study was 45 taken by the method of saturated samples. Data obtained by distributing questionnaires to the respondents. Score results of the questionnaire tested for validity and reliability. Data were analyzed using classical assumption test and multiple regression analysis, t test, F test, test the coefficient of determination. The results of the study obtained the following results: (1) participation budgeting significant effect on employee performance. T test results obtained value of t = 3.418 at the significance level of 5% (p <0.05). The test results obtained determination coefficient R2 value of 0.250, meaning that about 25% of the variability of employee performance can be explained by the variable budgeting participation; (2) the interaction of budgetary participation and organizational commitment to employee performance. The results of multiple regression analysis obtained tcount for interaction budgetary participation and organizational commitment of 1,283 at the 5% significance level. This means that organizational commitment is not moderating variables that moderate the relationship between budgeting participation with employee performance; (3) interaction budgetary participation and leadership style on employee performance. The results of multiple regression analysis obtained tcount for interaction budgetary participation and leadership style of -0.877 at significance level of 5%. That is the style of leadership is not a moderating variables that moderate the relationship between budgeting participation with employee performance.